Pānanāṃ bīḍāṃ - Dave, Jyotīndra H. (Gūrjara Grantharatna Kāryālaya, 2011)
Humorous articles based on various themes
Humors. - Reprint. Originally published: 1946. - In Gujarati-Schr
Keywords: Gujarati wit and humor